The Effect of Compensation and Workload on Turnover Intention at PT Musindo Laksana Guna - Priska Tobing; Yupiter Yancik; Dwi Rachmawati (International Publisher (YAPENBI), 2025)
This study aims to determine impact of compensation and workload on turnover intention among employees of PT Musindo Laksana Guna. A quantitative methodology was applied in this study, employing questionnaires to collect information from 30 actively working employees using saturated sampling techniques. Statistical analyses, such as t-tests, f-tests, and R². Data analysis was performed using multiple linear regression using SPSS version 27. The results showed that H1: “Compensation partially negatively affects turnover intention at PT Musindo Laksana Guna”; H2: “Workload partially positively affects turnover intention at PT Musindo Laksana Guna”; and H3: “Compensation and workload simultaneously affect turnover intention at PT Musindo Laksana Guna”. With an Adjusted R² value of 0.603, the model explains 60.3% of the changes in turnover intention through compensation and workload, leaving 39.7% influenced by factors outside the present analysis.